PENGARUH PROFITABILITAS, PERUBAHAN PAJAK, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze the influence of profitability, tax changes, growth of the Companyand Company Size for Funding Decisionson Manufacturing Companies listed on the Indonesia Stock Exchange. The populationin this study are 100 companies listed in Indonesia Stock Exchange in 2010-2013. The sample selection is done by purposive sampling method. Mechanical testing of the data is by using multiple linear regression analysis.The results of analysis show that the variable profitability, tax changes and growth of the company significant positive effect on financing decisions, while the size of the company significant negative effect on funding decisionson Manufacturing Companies listed onthe Indonesia Stock Exchange.Keywords: Profitability, Tax Reform, Growth Company, Company Size and Funding Decisions